Non-Nominal HIV Surveillance: Preserving Privacy While Tracking an Epidemic - Patrick, David M. (Can J Public Health, 1999)
Objective: To enhance HIV surveillance within a non-nominal provincial testing system. Methods: Confirmatory HIV tests from a provincial laboratory were analyzed during 1995 and 1996. Enhancements included elimination of repeat positive tests for the same individual using automated matching of non-nominal identifiers and nurse call-back of health care providers, completion of missing information through call-back and connection of providers with resources for patient care. Results: Forty-seven percent of 2,683 reactive HIV tests were identified as duplicates for the same individual, meaning that 1,401 people tested positive for the first time. From laboratory test data to enhanced unduplicated data after call-back, the proportion of tests for which risk and ethnic information was unknown dropped from 37% to 11% and from 64% to 18% respectively (p<0.0001). Conclusions: Enhanced non-nominal surveillance for HIV is a practical means of marrying the needs of public health for epidemiological information and the rights of patients to privacy.